Evaluation of DeChoker, an Airway Clearance Device (ACD) Used in Adult Choking Emergencies Within the Adult Care Home Sector: A Mixed Methods Case Study - Bhavik G. Bhanderi; Sue Palmer Hill (Frontiers Media S.A., 2020)
Foreign Body Airway Obstruction (FBAO) is a medical emergency that can result in death, particularly if swift, appropriate action is not taken. It can be a frightening experience for all involved. DeChoker, an Airway Clearance Device (ACD), might provide an additional alternative in the management of choking; however, limited evidence around its safety and effectiveness makes adoption controversial.Objectives: An independent evaluation to explore the experiences of health and care professionals who used DeChoker in real-life adult choking emergencies, focusing on the product's safety, efficacy and ease of application.Design: Retrospective mixed methods case study, with multiple embedded units of analysis.Setting: UK adult care homes.Participants: Twenty seven incidents of adult choking emergencies self-reported by care home staff where DeChoker was used. This data was augmented by an in-depth exploration of four individual choking incidences.Results: The choking victim's ages range: 45 to 101 years (mean 79.8 years). The device was reported to have successfully removed the obstruction in 26 of 27 cases, with very few complications or adverse events reported. In 21 of 27 incidents (78%) the victim was not required to visit Accident and Emergency. Qualitative data indicated nursing home staff found the DeChoker easy to use and valued its presence as an adjunct to current guideline procedures.Conclusion: There is a dearth of evidence surrounding the management of choking and little innovation in this area for five decades. This retrospective evaluation contributes to discussion regarding the role ACDs might play in the management of choking, particularly in cases where current choking management guidance are ineffective, insufficient, inappropriate or impractical (e.g., frail or movement restricted people). The interview data presents a view from care home staff that the DeChoker, as an ACD, contributed to saving the life of choking victims.